Greater Rupture Risk for Familial as Compared to Sporadic Unruptured Intracranial Aneurysms - Broderick, Joseph P.; Brown, Robert D.; Sauerbeck, Laura; Hornung, Richard; Huston, John; Woo, Daniel; Anderson, Craig; Rouleau, Guy; Kleindorfer, Dawn; Flaherty, Matthew L.; Meissner, Irene; Foroud, Tatiana; et al. (Stroke (1970), 2009)
Background and Purpose— The risk of intracranial aneurysm (IA) rupture in asymptomatic members of families who have multiple affected individuals is not known. Methods— First-degree unaffected relatives of those with a familial history of IA who had a history of smoking or hypertension but no known IA were offered cerebral MR angiography (MRA) and followed yearly as part of a National Institute of Neurological Diseases and Stroke-funded study of familial IA (Familial Intracranial Aneurysm [FIA] Study). Results— A total of 2874 subjects from 542 FIA Study families were enrolled. After study enrollment, MRAs were performed in 548 FIA Study family members with no known history of IA. Of these 548 subjects, 113 subjects (20.6%) had 148 IAs by MRA of whom 5 subjects had IA ≥7 mm. Two subjects with an unruptured IA by MRA/CT angiography (3-mm and 4-mm anterior communicating artery) subsequently had rupture of their IA. This represents an annual rate of 1.2 ruptures per 100 subjects (1.2% per year; 95% CI, 0.14% to 4.3% per year). None of the 435 subjects with a negative MRA have had a ruptured IA. Survival curves between the MRA-positive and -negative cohorts were significantly different ( P =0.004). This rupture rate of unruptured IA in the FIA Study cohort of 1.2% per year is approximately 17 times higher than the rupture rate for subjects with an unruptured IA in the International Study of Unruptured Aneurysm Study with a matched distribution of IA size and location 0.069% per year. Conclusions— Small unruptured IAs in patients from FIA Study families may have a higher risk of rupture than sporadic unruptured IAs of similar size, which should be considered in the management of these patients.